Innovative performance development model based on human capital and network quality toward improved marketing performance - Prima Sandri; Widodo (Management Science Letters, 2019)
This study seeks to explore how innovative performance development model, which is based on human capital and network quality, can contribute to the improvement of marketing performance. Respondents are the chief executives of Pertamina lubricants distributors, with sample size of 120 out of 460. For the analysis, the Struc-tural Equation Model (SEM) is applied along with AMOS software. The result of the study shows that there was improvement on marketing performance through the implementation of innovative performance management based on network quality.